Advances in Transportation Geotechnics IV Proceedings of the 4th International Conference on Transportation Geotechnics Volume 3 - Tutumluer, Erol.; Nazarian, Soheil; Al-Qadi, Imad.; Qamhia, Issam I.A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This volume presents selected papers presented during the 4th International Conference on Transportation Geotechnics (ICTG). The papers address the geotechnical challenges in design, construction, maintenance, monitoring, and upgrading of roads, railways, airfields, and harbor facilities and other ground transportation infrastructure with the goal of providing safe, economic, environmental, reliable and sustainable infrastructures. This volume will be of interest to postgraduate students, academics, researchers, and consultants working in the field of civil and transport infrastructure. .
Chapter 1: Investigation on the dynamic response of a high-speed railway tunnel located beneath an airport runway and uneven settlement of the runway -- Chapter 2: Influence of shield slurry property on filter cake quality in sand stratum -- Chapter 3: Dynamic response and long-term settlement of four overlapping tunnels subject to train load -- Chapter 4: Dynamic stability of soft soil between closely and obliquely overlapped metro tunnels subjected to moving train loads -- Chapter 5: Research on Calculating Quantity of Utility Tunnel with Revit Secondary Development -- Chapter 6: The influence of variation in groundwater table on ground vibrations from underground tunnels -- Chapter 7: Experimental studies on three types of vibration isolators for the buildings near subways -- Chapter 8: Dynamical response of floating slab track with variation on failure position of steel spring -- Chapter 9: The effect of boundary permeability to the dynamic response of the layered saturated ground under a moving load in a tunnel -- Chapter 10: The effect of excavation unloading on the deformation of existing underlying shield tunnel.
Keywords: Engineering geology; Geotechnical engineering; Transportation engineering; Traffic engineering; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Transportation Technology and Traffic Engineering; Engineering geology -- Congresses; Transportation engineering -- Congresses